Alteration of flow regimes caused by large‐scale forest disturbance: a case study from a large watershed in the interior of British Columbia, Canada. Issue 2 (24th February 2013) - Zhang, Mingfang; Wei, Xiaohua
ABSTRACT Forest disturbance can greatly alter flow regimes and consequently the structures and functions of ecosystems. However, the impacts of forest disturbance on flow regimes have rarely been investigated in large watersheds. In this study, we used a large severely disturbed watershed, the Baker Creek watershed located in the central interior of British Columbia, Canada, to examine how forest disturbance altered the flow regimes and to discuss the possible ecological implications of these alterations. Equivalent clear‐cut area, an indicator combining all types of forest disturbances and accounting for hydrological recovery, was adopted to represent the cumulative forest disturbance levels over time at a watershed scale. Flow duration curves and time series cross‐correlation analysis were used to detect the statistical significance of relationships between flow regimes (magnitude, duration, timing, frequency and variability of high flows and low flows) and forest disturbance (clear‐cut area). The results showed that the magnitude of high flows was significantly increased and the timing of high flows was significantly advanced by forest disturbance. After forest disturbance, the occurrence of high flows with greater return periods became more frequent with increased variations. In addition, forest disturbance significantly increased the magnitude of low flows but with reduced variability. On average, high flows and low flows in the disturbed period were 31·4% and 16·0% greater than those in the reference period, respectively. Possible ecological implications of these hydrological alterations caused by forest disturbance were also discussed. Copyright © 2013 John Wiley & Sons, Ltd.